PARTICIPATION OF FARMER ORGANIZATIONS IN THE OPERATION AND MAINTENANCE OF TERTIARY IRRIGATION NETWORK IN MANGKUTANA DISTRICT - Yusuf, Riani; Mauliana, Deasy (Jurnal Administrasi Negara, 2023)
Mangkutana District with a majority farmer population and has 2,383 HA of irrigated rice fields, so the Farmers of Water user Group (P3A) as a direct beneficiary of irrigation services is needed to take part in the management and maintenance of maximum irrigation networks. This study aims to determine the participation of P3A in the operation and maintenance of tertiary irrigation networks in Mangkutana District. The research method uses a qualitative descriptive method. Primary data is obtained through direct observation by interview and observation. While secondary data through document review related to the research. This research analyzes the participation of P3A in the operation and maintenance of irrigation networks starting from the participation in the planning, implementation, benefit taking and supervision stages. The results showed that P3A participation in the planning stage was generally good. In participation in the implementation stage, the indicator of compliance with irrigation service fees is very lacking because the majority of P3As have never collected dues either in the form of money or in the form of grain. P3A participation in the stages of receiving and utilizing the results of irrigation network OP activities is classified as good. At the stage of participation in the monitoring and assessment of results, P3A is less involved in routine inspections for evaluation of irrigation networks due to the limited ability of farmers to assess irrigation networks. In order to increase the capacity of P3A participation and maintain the sustainability of farmer participation in the operation and maintenance of irrigation networks, there needs to be policy support to allocate financing for the management of tertiary irrigation networks provided to P3A which has the authority to manage tertiary irrigation. This is certainly implemented with an approach mechanism that empowers the institutional capacity of P3A.